Descriptive Investigation of Strongyloidiasis Infection and Characterization of Strongyloides stercoralis Using Morphological and Molecular-Based Methods - Nayana Gunathilaka; Nilmini Chandrasena; Tharaka Wijerathna; Yoshito Fuji; Deepa Gunasekara; Ruwan Prasanna Gunatilaka; Ranjan Premaratna (Case Reports in Infectious Diseases)
Strongyloidiasis is caused by the nematode Strongyloides stercoralis which has the unique ability to reproduce and complete its entire life cycle within the human host through its autoinfection cycle. Diagnosis of this infection is important because of its potential to cause fatal hyperinfection syndrome or disseminated infections in those with defective cellular immunity. Parasitological methods based on faecal microscopy and culture often fail to detect low-intensity infections. A multiplex polymerase chain reaction (PCR) assay was developed for the detection of S. stercoralis, Ascaris lumbricoides, and Enterobius vermicularis by designing primers specific for the ITS1 region of ribosomal DNA of S. stercoralis and A. lumbricoides and 18S region of rRNA of E. vermicularis. A 61-year-old patient presented with chronic gastrointestinal and respiratory symptoms and weight loss with a stool microscopy positive for helminth larvae. Stool cultures with the Harada–Mori technique yielded L3 larvae which were identified as S. stercoralis based on morphology. The multiplex PCR performed on DNA extracted from stool elicited the expected band at 129 bp on gel electrophoresis of the PCR yield providing molecular evidence of intestinal strongyloidiasis. The patient’s gastrointestinal symptoms improved with a six-day course of albendazole (400 mg twice daily). Negative posttreatment stool microscopy, culture, and PCR confirmed successful clearance of infection. Molecular-based PCR assay is a promising tool to diagnose and assess the therapeutic efficacy of anthelmintics in intestinal helminthiases such as strongyloidiasis.